Varieties of censorship: Hate speech, pornography, and the First Amendment. Issue 2 (3rd July 2021) - Federman, Cary
ABSTRACT: Until the 1960s, governmental limits on speech and expression, particularly around issues of pornography and obscenity, were common. These restrictions were enacted to reinforce a set of standards that had broad support among the American people. Since the 1960s, we have seen a great expansion of the right to free speech and expression. Today, however, the libertarian consensus has fractured. The new censorship that favors regulating hate speech confronts the underlying premises of the old censorship. Rather than comparing and contrasting the libertarian position with the censorship of hate speech position, as is so often done, in this article, I will compare and contrast two pro-censorship positions, one group favoring the censorship of hate speech, the other favoring the censorship of pornography and obscenity. My purpose is not to advocate for censorship. Rather, my idea is to examine and explain the different rationales that exist in the two opposing approaches to censorship, to better judge the merits of censorship and free speech.